Biomimetic photocatalytic sulfonation of alkenes to access β-ketosulfones with single-atom iron site. Issue 1 (6th December 2019) - Wen, Jiangwei; Yang, Xiaoting; Sun, Zongzhao; Yang, Jianjing; Han, Ping; Liu, Qiuxia; Dong, Hongyan; Gu, Meng; Huang, Limin; Wang, Hua
Abstract : A biomimetic photocatalyst of single-atom iron site (CNH) has been initially fabricated through coupling carbon nitride with hemin for the visible light-promoted sulfonation of alkenes to access β-ketosulfones. Abstract : Biomimetic photocatalysis as an important organic transformation strategy has received increasing attention, with the performances of biomimetic catalysts largely depending on their design. This protocol has been initially used to fabricate a biomimetic photocatalyst of single-atom iron site through coupling carbon nitride with hemin (CNH) for the visible light-promoted sulfonation of alkenes to produce β-ketosulfones with up to 94% yield. The experimental results show that the role of CN in CNH is concentrated on enhancing the separation ability of photogenerated electron pairs and holes to improve the photocatalytic activity and stability. Moreover, the as-prepared photocatalyst of single atom iron can be irradiated under near-infrared light with a satisfactory yield, and is also feasible for the sulfonation reactions of androstenones. Importantly, this biomimetic catalysis-based synthesis system has some merits, namely high catalysis efficiency, favorable recyclability, high turnover number, and excellent functional group tolerance, making it promising for extensive applications in organic transformations for the synthesis of β-ketosulfones to access various bioactive drugs.